Investigating the use of generational cohort theory to identify total reward preferences - Davids, Aayesha (School of Management Studies, 2020)
Background: Anecdotal accounts of stereotypes and/or generalisations about perceived generational differences within the workplace have become commonplace. Generational cohort theories are often used to identify generational cohorts of employees that are argued to be different, including having differing expectations, needs, preferences and even values. In addressing and/or accommodating such individual differences organisations are increasingly adopting strategies and interventions that take such generational differences amongst employees into account (Costanza & Finkelstein, 2015). Addressing generational differences within the workplace has particularly become popular in the design and implementation of total reward or remuneration and recognition strategies, policies and practices. Understanding generational and/or demographic characteristics, specifically differences, that create distinct cohorts allow organisations to design reward and recognition packages that create distinctly unique value for their employees. Offering tailored or more focused reward strategies and practices, designed with individual differences in mind are believed to enhance attraction, employee engagement and retention and so allow an organisation to bolster its competitive advantage and contribute to sustained organisational success (Snelgar, Renard, & Venter, 2013). In support of this notion, empirical studies are showing promising results for targeted reward strategies and practices. Rationale for the Research Study Effective talent management, i.e. attracting, engaging and retaining sought-after highly skilled employees is critical for the success of any organisation. However, organisations are increasingly experiencing challenges in recruiting, motivating and retaining scarce human capital, colloquially referred to as talent (Barkhuizen, 2014). Failure on the part of organisations to understand and adapt to differences in the workforce may result in them not being able to attract the talent required; keep employees motivated and engaged; and experience unintended employee turnover which is associated with notable direct and indirect costs for them (Westerman & Yamamura, 2007). Organisations, therefore, are constantly searching for new and innovative approaches to more effectively attract, retain and engage employees (Snelgar et al., 2013). There is a growing body of research (Haynes, 2011; Snelgar, Renard, & Venter, 2013) that has shown that identifying distinct reward and recognition preferences amongst cohorts of employees and targeting reward and recognition strategies accordingly, is showing promising potential in this regard. When designing and implementing targeted approaches to reward and recognition, employee cohorts are most often identified using generational cohort theory, i.e. using various established guidelines to group employees into generational cohorts that are believed to be distinctly different to one another, while those within these groups being more similar than not. Results obtained from studies using these various employee cohorts as a framework have been used to inform the design of targeted reward and recognition practices and policies. Generational cohort theory is, however, mostly grounded on a set of historical events that took place in the United States of America (USA). Despite this, the American-based framework used to identify individuals belonging to various generations has been adopted globally, both within organisations and even used in research studies published in peer-reviewed literature. However, several authors have criticised the indiscriminate use of a popular American-based generational framework, i.e. focusing on events affecting Americans arguing that this has resulted in a somewhat narrow or even skewed view generational cohorts. These authors have gone as far as to argue that the American-based generational framework may not be appropriate or ineffective outside of the USA at all (Close, 2015). Following this reasoning, they have called for alternative frameworks that create distinct generational cohorts relevant in contexts outside of America, i.e. based on different events and criteria more applicable to those contexts. Aim of the research study The aim of the present study was to investigate the reward preferences of a broad range of employees in an effort to assess whether the popular generational model of Strauss and Howe (1991) is relevant and/or as effective in a non-American context, as well as to possibly find support for alternative perspectives or approaches to identify distinct generational cohorts in organisations that may be more appropriate and/or effective when designing reward offerings for different cohorts of employees. Given time and cost constraints, South Africa was chosen to investigate this claim given that it is a developing economy (vs the USA being a developed economy) and has a different set of notable events that have shaped its history to that which is applicable to the USA. Given the aim of the present study, an exploratory research design was considered most appropriate to investigate generational cohort theory within a non-American context as a framework to identify employee groups/cohorts that have distinctly different total reward preferences. For the purposes of the present study, it was decided that a quantitative approach would be followed as it is most useful to draw conclusions or inferences related to the total reward preferences of employee groups/cohorts. The present study followed a non–probability or convenience sampling approach with a realised sample of 169 respondents. The majority of respondents were Coloured and were further female, with majority of attaining a qualification post matric. Main results and findings A one-way Analysis of Variance (ANOVA) revealed no statistically significant difference between the generational groups based on the popular generational model of Strauss and Howe (1991), nor for a proposed generational cohort framework that was designed for the purposes of the present study and which was based on notable South African historical events. Following a data-driven exploratory approach, cluster analysis, on the other hand, yielded three distinct generational cohorts based on their perceived reward preferences for typical total rewards elements. Significant differences in the total reward preferences of respondents born after 1994 and those before 1994. Choice-based modelling (choice-based conjoint analysis) revealed that most respondents considered financial rewards as being the two most preferred total reward elements for them, including remuneration (guaranteed pay) followed by benefits and then non-financial rewards (work-life balance being the most preferred non-financial reward preference). Theoretical and Practical Implications Numerous research studies have made use of the popular American-based generational model to identify the reward preferences of cohort groups, without taking into account context-specific variables. There is further a dearth of empirical research that has been conducted to investigate generational cohort theory specifically, while none were found that were conducted in developing economies, such as South Africa. The present study address this gap in current literature. The use of choice-based modelling or choice-based conjoint analysis, furthermore, makes a methodological contribution given that this method is seldom found in total reward preference studies. This method was shown to identify total reward preferences that could not be determined using a field-survey or questionnaire. Choice-based modelling is different to typical survey approaches in that it is better able to replicate human decision making, i.e. assessing relative importance of attributes and levels based on combinations of choices and related sacrifices that humans deal with when making a choice-decision. In terms of the practical contribution of the present study, the results provide insights for organisations that may be incorporated when designing differentiated total reward strategies to accommodate and/or address the needs of the different generational groups.